Credit scoring data for information asset analysis - Silva, Fábio (2011)
Risk assessment is an important topic for financial institution nowadays, especially in the context of loan applications. Some of these institutions have already implemented their own credit scoring mechanisms to evaluate their clients’ risk and decide based in this indicator. In fact, the information gathered by financial institutions constitutes a valuable source of data for the creation of information assets from which credit scoring mechanisms can be developed. The purpose of this paper is to, from information assets, create a decision mechanism that is able to evaluate a client’s risk. Furthermore, upon this decision mechanism, a suggestive algorithm is presented to better explain and give insights on how the decision mechanism values attributes.